Effects of a tapering period on physical condition in soccer players - Beltran-Valls, M. R.; Camarero-López, G.; Beltran-Garrido, J. V.; Cecilia-Gallego, P. (The Journal of Strength and Conditioning Research, 2020)
The aim of this research was to analyze the effects of a 2-week step tapering period on lower-limb muscle power, change of direction (COD) and acceleration capacities, and on the stress-recovery state in an amateur soccer team. Twenty-two male players were included in the study. After a 6-week progressive training, the sample was divided into experimental group (EG) (n = 11), which did a 2-week period of taper in which training volume was 50% reduced (intensity was kept high) and control group (CG) (n = 11), which kept on with the training. Muscle power (countermovement jump test), acceleration (10-m sprint test), COD (Illinois test), and stress and recovery perceptions (RESTQ questionnaire) were evaluated before training, at the end of it (pretapering, PRE-TP) and after the tapering period (posttapering, POST-TP). After the taper, the EG in comparison with the CG showed significantly improved power (1,029.71 ± 108.51 W/kg vs. 1,084.21 ± 110.87 W/kg; p = 0.01), acceleration (1.72 ± 0.09 seconds vs. 1.67 ± 0.07 seconds; p = 0.05), and lower stress levels (1.9 ± 0.5 vs. 1.6 ± 0.5; p = 0.01) (PRE-TP vs. POST-TP, respectively). Change of direction did not show significant changes. In conclusion, a 2-week step tapering program was found to be an effective periodization strategy to increase muscle power and acceleration, and to reduce stress perception in soccer amateur players.